The origins of the First World War : diplomatic and military documents - Mombauer, Annika (Documents in modern history., 2013)
A unique collection of hundreds of diplomatic and military documents on the origins of WWI: newly-discovered archival sources as well as documents not previously available in English. It includes a comprehensive scholarly introduction covering the most controversial issues in the debate on the origins of WWI on the eve of the centenary.